The Terrible Plop - Dubosarsky, Ursula; Joyner, Andrew (Australia : Puffin Books, 2017)
When a mysterious sound sends the whole forest running away in fear, only the littlest rabbit is courageous enough to discover what really happened.
K-3.
English.
Keywords: Courage -- Fiction; Fear -- Fiction; Forest animals -- Fiction; Apple -- Fiction; Bear -- Fiction; Rabbit -- Fiction